Problems faced by libyan government acting as property managers in managing and maintaining residential - Emhemed Alhemri, Zakarya Ibrahim (2008)

(untitled)
In recent years, more Libyans are moving into stratified unit, especially in urban centres due to limited land availability. Thus, there is a greater awareness of the need for these properties to be well-managed. Property management has historically been underrated and is often associated with mundane maintenance work. However, with the increasing development of strata titled property and legislation to govern the property management of such property, there has been an increasing demand for professional property management skills. Therefore, this study has been developed with the aim to identify the main problems related to property management and the issue in managing the high rise and residential in Libya. The study was conducted through structured interview with professional property managers, and also through postal questionnaires. From the study, it was found that the most common complaint lodge by tenants in high rise is defects in their unit not attended within time specified. The process and procedures of handling defects complaint from tenants are also inefficient. The most common problem faced by property management is poor collection of maintenance fee. The tenants do not pay up the maintenance fee because they are not satisfied with the maintenance work carried out by property management.